Paratesticular rhabdomyosarcoma - A case report (Grande Medical Journal, 2019)
Rhabdomyosarcoma is a malignant tumor of muscular origin. It comprises the most common soft tissue tumor in children accounting for approximately 5-8% of childhood cancers. Here we present a case of paratesticular rhabdomyosarcoma in a 13-year male child who was referred for ultrasonic examination (USG) to the department of radiology for evaluation of right scrotal swelling with pain for few months. Paratesticular rhabdomyosarcoma is a rare non germ cell tumor of scrotal sac in children and young adult/teens which can invade testis at presentation. We review the epidemiology, histology, clinical presentation, staging and prognosis of paratesticular rhabdomyosarcoma and discuss the role of radiology in their management.